Understanding environments - Codrington Stephen B 1953 (Cambridge ; New York, NY, USA : Cambridge University Press, 1995)
Presents information for analyzing the world's major biophysical environments and the processes which govern them; then explores environmental management through case studies from around the world.
Includes index.
Keywords: Environmental sciences -- Study and teaching -- Juvenile literature; Environmental sciences; Environmental policy